Adopting industrialisation in the construction environment: meeting the requirements of sustainability / Muhamad Faiz Musa …[et al.] - Musa, Muhamad Faiz; Yusof, Mohd Reeza; Samsudin, Noor Sahidah; Muhamad Halil, Faridah (Universiti Teknologi MARA Shah Alam, 2016)
The construction industry should move from conventional construction method and adopt the industrialisation concept, to increase productivity and deliver quality construction end products. Industrialisation is the combination of a large market to divide into fractions the investment in strategies and innovation, in return, of simplifying the production and, therefore, reducing the costs. The introduction of Degree of Industrialisation by Roger-Bruno Richard is critical to the construction industry. The five degrees of industrialisation are prefabrication, mechanisation, automation, robotics and reproduction. Richard’s Degree of Industrialisation is in line with the Malaysian government’s vision to be a developed nation by 2020, to push forward the use of innovative technologies in most industries including the construction industry. The adoption of industrialisation and innovations in the Malaysian construction industry has the potential to solve the current problems in the construction industry. The problems are the inferior quality of products and processes, a poor site working conditions, low construction productivity, high construction cost, relying on foreign workers and lack of skill labours. The adoption of industrialisation and innovations promote sustainability in the construction environment. The objectives of the study are to investigate whether the adoption of industrialisation in the construction environment promotes sustainability and to identify the current level of industrialisation of the Malaysian construction industry. The methodologies of the study are semi-structure interview and observation. The Malaysian construction industry is ready to embrace industrialisation in construction environment in limited areas and industrialisation promotes sustainability in the construction environment.